2022
DOI: 10.1177/23969873221094412
|View full text |Cite
|
Sign up to set email alerts
|

Lobar intracerebral hemorrhage and risk of subsequent uncontrolled blood pressure

Abstract: Background: Uncontrolled blood pressure (BP) in intracerebral hemorrhage (ICH) survivors is common and associated with adverse clinical outcomes. We investigated whether characteristics of the ICH itself were associated with uncontrolled BP at follow-up. Methods: Subjects were consecutive patients aged ⩾18 years with primary ICH enrolled in the prospective longitudinal ICH study at Massachusetts General Hospital between 1994 and 2015. We assessed the prevalence of uncontrolled BP (mean BP ⩾140/90 mmHg) 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Studies showed that a minority of survivors achieved adequate BP control, with suboptimal BP control in more than 50% of ICH survivors 19,20 . Poor BP control might be explained by undertreatment ‐especially in lobar ICH survivors‐ or by resistant hypertension more often found in Black, Hispanic and Asian people 20,30 . There is limited evidence about the optimal antihypertensive drugs to use after ICH events.…”
Section: Blood Pressure Loweringmentioning
confidence: 99%
“…Studies showed that a minority of survivors achieved adequate BP control, with suboptimal BP control in more than 50% of ICH survivors 19,20 . Poor BP control might be explained by undertreatment ‐especially in lobar ICH survivors‐ or by resistant hypertension more often found in Black, Hispanic and Asian people 20,30 . There is limited evidence about the optimal antihypertensive drugs to use after ICH events.…”
Section: Blood Pressure Loweringmentioning
confidence: 99%